2009
DOI: 10.1007/s10735-009-9220-7
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of thymoquinone on streptozotocin-induced diabetic nephropathy

Abstract: The aim of this study was designed to investigate the possible beneficial effects of the thymoquinone (TQ) in streptozotocine (STZ)-induced diabetes in rats. The rats were randomly allotted into one of three experimental groups: A (control), B (diabetic untreated), and C (diabetic treated with TQ); each group contain ten animals. B and C groups received STZ. Diabetes was induced in two groups by a single intra-peritoneal (i.p) injection of STZ (50 mg/kg, freshly dissolved in 5 mmol/l citrate buffer, pH 4.5). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
53
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 55 publications
7
53
0
Order By: Relevance
“…TQ therapy also causes renal morphologic and functional improvement after STZ-induced diabetes in rats. When TQ (50 mg/kg/day) was given for 12 weeks to STZ induced diabetic rats, three days after induction of diabetes, it reduced the glomerular size, thickening of capsular, glomerular and tubular basement membranes, increased amounts of mesangial matrix and tubular dilatation and renal function as compared with diabetics untreated [46]. During pregnancy of diabetic (STZ induced) mice, TQ treatment inhibits the rate of embryo malformations by reducing the free radicals, in addition to increasing the size and maturation of embryos [47].…”
Section: Antidiabetic Activity In Stz Induced Diabetic Ratsmentioning
confidence: 98%
“…TQ therapy also causes renal morphologic and functional improvement after STZ-induced diabetes in rats. When TQ (50 mg/kg/day) was given for 12 weeks to STZ induced diabetic rats, three days after induction of diabetes, it reduced the glomerular size, thickening of capsular, glomerular and tubular basement membranes, increased amounts of mesangial matrix and tubular dilatation and renal function as compared with diabetics untreated [46]. During pregnancy of diabetic (STZ induced) mice, TQ treatment inhibits the rate of embryo malformations by reducing the free radicals, in addition to increasing the size and maturation of embryos [47].…”
Section: Antidiabetic Activity In Stz Induced Diabetic Ratsmentioning
confidence: 98%
“…It has been reported that DN occurs in approximately 30-40% of diabetes mellitus type 1 (DM-1) [26] cases and is the major cause of death in diabetics. The mechanism of glomerular pathology underlying in DN is still unclear [27]. There is evidence showing that diabetic nephropathy results from metabolic alterations that occur in the renal glomeruli after long exposure to high glycaemic levels [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence showing that diabetic nephropathy results from metabolic alterations that occur in the renal glomeruli after long exposure to high glycaemic levels [28,29]. In addition to the haemodynamic effects, several non-haemodynamic factors have been identified to be involved in the pathogenesis of DN [27].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Hawsawi et al reported that TQ reduces blood glucose levels in normal rats, [17] and similar results were reported in normal and alloxan-induced diabetic rabbits, alloxan-induced diabetic rats, and human subjects. [18][19][20][21] However, 2 different studies reported that TQ did not change fasting blood glucose levels significantly in normal or streptozotocin-induced diabetic rats. [22,23] Although the reason for these differing effects is unclear, TQ might cause hypoglycemia in 2 ways.…”
Section: Discussionmentioning
confidence: 99%
“…[24] In another study, Kanter et al reported that TQ had protective therapeutic effects on diabetes by decreasing oxidative stress and preserving pancreatic β-cell integrity; therefore, the authors concluded that TQ might be useful clinically for protecting β-cells from oxidative stress. [25] TQ exerts gastroprotective and hepatoprotective effects on the gastrointestinal system. A previous study reported that TQ could protect gastric mucosa from acute alcohol-induced mucosal injury, and that this gastroprotective effect might be induced by its radical-scavenging activity.…”
Section: Discussionmentioning
confidence: 99%